Cultivation and uses of fish stem cells - Глушко, Ю. М.; Бєлікова, О. Ю.; Суховерська, Л. П.; Алєксєєва, Ю. С. (Problems of Environmental Biotechnology, 2019)
Stem cells have great potential for studying the processes of cells differentiation and provide the opportunity to find the relationship between in vitro and in vivo manipulation with genome. Application of fish embryonic stem cells provides the opportunity to combine embryological and molecular-genetic studies of vertebrate’s development. The article is dedicated to comparative analysis of modern biotechnologies fish stem cells and valuation of the prospects for using these cells in medical genetics and other areas of scientific activity.